Elemen-Elemen Hermeneutika dalam Penafsiran Quraish Shihab : Telaaah Atas Buku Wawasan al-Qur’an : Tafsir Maudhu’i Berbagai Persoalan Umat: Telaah Atas Buku Wawasan al-Qur’an Tafsir Maudhu’i Berbagai Persoalan Umat - Humamurrizqi (Al Irfani: Journal of Al Qur'anic and Tafsir, 2020)
Although the Quraish Shihab in its interpretation practice does not mention the term hermeneutic, but if it is observed in the interpretation practice, the Quraish Shihab has practiced how the hermeneutic work steps itself. The hermeneutic nuance that is very prominent in its interpretation is first, exposure to the macro context, in this context is the presentation of the history of women before the descent of the Koran, secondly, the exposure related to correlation (munasabah) verse one with the other and the third exposure related to the opinions of salafus shalih (the predecessors) who indeed have the capacity in the realm of study of interpretation, fourth, the contextualization and re-actualization efforts of the verse with the present context. Using this hermeneutic aspect, in the end the Quraish Shihab asserted that the Qur'an as a guide has placed and placed women in their proper place, sex differences do not become differences in position or glory. There is no term for women to be dominated by men, both men and women remain and before God. The difference between the two is the quality of piety.